Implementation of CV Metha Developing Palembang Goods Ordering System - Fatmariani, Fatmariani; Putri, Meidyan Permata; Apriliani, Marhama (Politeknik Ganesha Medan, 2023)
Abstract CV Metha Berkembang is one of the companies engaged in the production and sale of aluminum sills. The sales process on CV Metha Berkembang has not been computerized where orders are made with consumers coming directly to the company's location or being able to call the company's phone number. An uncomputerized ordering process is needed in a company, where the ordering system does not require consumers to come to the place. For this reason, an ordering information system is needed that can make it easier for CV Metha Berkembang to carry out ordering activities. The system development method used is the prototype method, while for modeling the system used, namely flowcharts, data flow diagrams and entity relationship diagrams and conducting functional testing with blackbox testing. The result of this final project is in the form of a Website Application that aims to help the ordering process. This application is useful for the admin department to be able to confirm orders and input sold stock data. With this application, it can help consumers, leaders, managers, and admins in processing order data, sales stock, and total stock of goods.